IMPLEMENTASI PEMBELAJARAN ASWAJA NU DALAM MEMBENTUK PERILAKU KEAGAMAAN SISWA - Lilies Handayani; Imron Arifin (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
Aswaja is a way of thinking (Minhaj al-Fikr) in observing various problems in people's lives. This view leads the people of Nahdlatul Ulama to take action or behave according to religious guidance. For this reason, this research aims to determine the implementation, contribution and inhibiting, and supporting factors in Aswaja NU learning in shaping the religious behavior of Tebuireng Science Middle School students. This research uses a qualitative approach, with data collection through observation, interviews, and documentation studies as data collection techniques. This research shows that the implementation of Aswaja NU learning, which is carried out inside and outside the classroom, contributes to shaping students' religious behavior by deepening the material and daily practice. The inhibiting factor for learning Aswaja NU at SMP Sains Tebuireng is the lack of reading literature.